Legados e impactos desportivos dos Jogos Olímpicos - Rio 2016, um estudo de caso do Programa Esporte e Lazer da Cidade - Unidade Mangueira - André Felipe Nogueira Seixas (2018)
The opportunity that the city of Rio de Janeiro has had in hosting mega sport events, with an emphasis on the Olympic Games, makes us wake up to the importance of a place becoming a focus of attention and investment. This work aims to identify and analyze the socio-educational and infrastructure legacy indicators of the "Programa de Esporte e Lazer da Cidade", Mangueira, which was in force from October 2015 to June 2018. The publications related to the theme of Physical Education and Social Sciences were searched. In the perspective of deepening the understanding of the concepts of impact and legacies in sports programs of leisure and participation, which added to the field research, made possible a greater sensitivity on what it was before and after the Olympic Games. In order to collect the data we used the interview as an instrument through the google drive platform, with teachers and coordinators of the unit in question, making use of the technique of content analysis for the due treatment of the information obtained. The legacies and sports impacts generated from the Olympic Games Rio 2016, were not perceived by the interviewees in this unit. The increase in the visibility of sport through the media has also not led to an increase in the demand for new participants.Keywords: